Genome sequence of Candidatus Arsenophonus lipopteni, the exclusive symbiont of a blood sucking fly Lipoptena cervi (Diptera: Hippoboscidae) - Nováková, Eva; Hypša, Václav; Nguyen, Petr; Husník, Filip; Darby, Alistair C (Standards in genomic sciences, 2016)
Candidatus Arsenophonus lipopteni (Enterobacteriaceae, Gammaproteobacteria) is an obligate intracellular symbiont of the blood feeding deer ked, Lipoptena cervi (Diptera: Hippoboscidae). The bacteria reside in specialized cells derived from host gut epithelia (bacteriocytes) forming a compact symbiotic organ (bacteriome). Compared to the closely related complex symbiotic system in the sheep ked, involving four bacterial species, Lipoptena cervi appears to maintain its symbiosis exclusively with Ca. Arsenophonus lipopteni. The genome of 836,724 bp and 24.8 % GC content codes for 667 predicted functional genes and bears the common characteristics of sequence economization coupled with obligate host-dependent lifestyle, e.g. reduced number of RNA genes along with the rRNA operon split, and strongly reduced metabolic capacity. Particularly, biosynthetic capacity for B vitamins possibly supplementing the host diet is highly compromised in Ca. Arsenophonus lipopteni. The gene sets are complete only for riboflavin (B2), pyridoxine (B6) and biotin (B7) implying the content of some B vitamins, e.g. thiamin, in the deer blood might be sufficient for the insect metabolic needs. The phylogenetic position within the spectrum of known Arsenophonus genomes and fundamental genomic features of Ca. Arsenophonus lipopteni indicate the obligate character of this symbiosis and its independent origin within Hippoboscidae.
Keywords: Tsetse; Hippoboscidae; Symbiosis; Arsenophonus